(untitled) (De Musica, 2023)
The first opera in the history of music based on the Don Giovanni’s subject, L’empio punito of Alessandro Melani was staged on February 17, 1669, in the Teatro Colonna in Rome. The setting is in an imaginary Greece and the characters have names that evoke the Italian literary tradition. The main character - Acrimante - departs very far from the analogous ones of the texts based on the same subject. L’empio punito also lacks many dramaturgical topoi of Don Giovanni’s tradition: family ties, honor, request for repentance. The libretto contains some topoi very common in the European theatrical tradition but missing in the previous texts on this subject: the dream, the sleeping, the false poison, the pact with the Devil. The dramaturgical core of the story (the disrespect to the dead in the form of a dinner invitation) represented the starting point, a reservoir from which to draw. The result is that libertinism, contempt for death, and the rules of honor are dried up, as it were, to give more space to spectacular ostentation, the power of figurative impact, and the charm of music.